Manganese toxicity, phosphorus and calcium in two varieties of perennial soybeans (Glycine javanica L.) - Souto, Sebastião Manhães; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse experiment was carried out to study the interference of phosphorus and calcium with symbiotic nitrogen fixation of two varieties of perennial soybean (Glycine Javanica L.) in soils with manganese toxicity. The same experiment explores the possibility of supplying the high demand for phosphorus and calcium during plant establishment by coating the seed with rockphosphate. The following conclusion were drawn: 1) Seed pelleting with rockphosphate (from Olinda) did not substitute for phosphorus fertilizer but it did increase calcium deficiency symptoms in very young plants. 2) Fertilization with phosphorus increased, significantly, nodule growth and total nitrogen in the plant but had no effect on nodule numbers of the amount of N fixed per unit of nodule weight. These effects were more pronounced with variety SP.1. 3) Calcium applied as gypsum increased nodule size but tended to decrease their number so that there was no significant effect on total nodule weight or nitrogen fixation. The amount of N fixed per unit nodule weight was also unaffected by calcium. 4) Phosphorus and calcium stimulated manganese absorption. The latter increasing translocation of this element from roots to the aerial portion of the plant. 5) In soil with manganese toxicity, the variety SP.1 produced higher nodule weights, more total nitrogen in plants and higher forage yields than did the variety Tinaroo. 6) The variety Tinaroo absorbed more manganese than variety SP.1, without evidencing differences in translocation. 7) Seed coating increased manganese absorption and reduced nodule weight and nitrogen fixation in the variety Tinaroo. The opposite occurred with the variety SP.1.